Is Momentum Trading Strategy Still Profitable? Evidence from the Stocks in S&P 500 Index in 2000–2015 - Martikainen, Antti (My University, 2016)
The topic of this master’s thesis is momentum trading strategy. The purpose of this thesis is to examine if 6-2, 12-2 and 12-7 momentum trading strategies are profitable in 2000–2015, when the portfolios are formed from the stocks of S&P 500 Index. The theoretical part of this thesis introduces market efficiency, earlier literature about momentum trading strategy, and some basic asset pricing models. The thesis continues with empirical examination. The empirical results show that only 12-7 momentum trading strategy gains a positive return in the examined period. It also outperforms S&P 500 Index return. However, 6-2 and 12-2 momentum strategies gain negative average returns. The average returns of the long-short portfolios are not statistically significant. The Five-Factor Model intercepts for the long-short portfolios are neither significant. However, the winner portfolios gain significant positive average return. The loser portfolios have statistically insignificant positive average return. In profitable momentum trading, the loser portfolios should have negative average return since they are traded in short position. After all, the empirical results show that momentum trading strategy is not profitable in the examined period. For later research about momentum strategy in the 21st century, it could be interesting to examine how these momentum trading strategies perform after a few years. Nobody knows how the markets will move in the future.
Keywords: momentum; trading strategy; S&P500; stocks; portfolio; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|